New understanding of crystal control and facet selectivity of titanium dioxide ruling photocatalytic performance - Teera Butburee (2019)
© 2019 The Royal Society of Chemistry. Engineering crystals of titanium dioxide (TiO2) to expose the most reactive facet has been proved to significantly improve its photocatalytic performance. While most TiO2 with facets reported in the past was in a particle form, herein we directly grow TiO2 with arbitrarily tunable facets onto a transparent conductive substrate. This could reduce interparticle boundaries, and thus suppress charge recombination and facilitate more efficient charge transport compared to particle-assembled films. Combined systematic experimental and theoretical (density functional theory, DFT) studies reveal that fluoride ions (F-) and protons (H+) could play a synergistic role in controlling TiO2 crystals in the way that F- ions change the crystal phase of TiO2 to anatase with low-index facets, while H+ ions increase the {001}/{101} ratio. Moreover, the reductive and oxidative sites of facets are clearly elucidated by selective photodeposition of a noble metal and metal oxide. Different photocatalytic tests manifested that the {001} facet, which is conventionally believed to be the most reactive facet, does not always show the highest performance. On the other hand, the facets' reactivity appeared to depend on the types of reactions (reduction or oxidation) and the co-existing synergy of facets. These findings would provide a clear understanding of the true factors controlling facets, and the true order of reactivity of each facet that has remained controversial, and pave a way to improve both the efficiency and selectivity of TiO2 in a wide variety of photocatalytic applications in the future.